Race against terror : chasing an Al Qaeda killer at the dawn of the forever war - Tapper, Jake (Atria Books, 2025)
"When federal prosecutors Dave Bitkower and Shreve Ariail get the call from the FBI that the Italians have known terrorist Spin Ghul in custody, they immediately recognize the stakes of the situation. Determined to deliver justice for the soldiers killed in combat, they must traverse the globe, uncovering facts and evidence from thousands of miles away on a remote battlefield in Afghanistan. Through intense reporting and meticulous recreation, from the battlefield to the courthouse, [this book] tells the story of a man radicalized to enact violence, of the courageous soldiers who risked their lives for each other, and the diverse set of law enforcement, intelligence, and military personnel who work tirelessly to stay one step ahead of disaster"--